Gender Norms and Intimate Partner Violence - Libertad Gonzalez; Núria Rodríguez-Planas (Institute of Labor Economics (IZA), 2021)
We study the relevance of gender norms in accounting for the incidence and intensity of domestic violence. We use data for 28 European countries from the 2012 EU survey on violence against women, and focus on first- and second-generation immigrant women. We find that, after controlling for country-of-residence fixed effects, as well as demographic characteristics and other source-country variables, higher gender equality in the country of ancestry is significantly associated with a lower risk of victimization in the host country. This suggests that gender norms may play an important role in explaining the incidence of intimate partner violence.
Keywords: I1; Z1; 330; immigrants; social norms; gender; domestic violence; epidemiological approach